Woodcarving in Podhale and the Phenomenon of the “School in Zakopane” Sculptures and Design - Katarzyna Chrudzimska-Uhera (Muzeológia a Kultúrne Dedičstvo)
Zakopane woodcarving is perceived in a kind of suspension between ethnographic tradition (folk art) and artistic modernity. For almost 250 years now, the patriotic aspect of Podhale’s tangible culture has been an inseparable context of its evaluation. For the Polish people, Zakopane and the Tatra Mountains are a phenomenon which is permanently inscribed in the cultural heritage of their nation. Based on the contemporary state of research and current methodologies, the article aims to revise the methods of researching, interpreting and exhibiting Zakopane sculptures, both historical and contemporary.